Training and Assistance for Accreditation Preparation for Raudhatul Athfal - Dewi Sri Suryanti; Eniwati Khaidir; Heldanita Heldanita (Perkumpulan Pengelola Jurnal (PPJ) PAUD Indonesia, 2023)
This Community Service aims to provide teachers, administrators or educational staff with understanding and skills in preparing for accreditation for Raudhatul Athfal in Pekanbaru City. This service method uses the ABCD (Asset Based Community Development) approach, which explores the strengths and competencies possessed by assisted residents. The results of this service are the socialization of the urgency and motivation of accreditation for each institution to improve in their respective schools with the aim of improving the quality and ranking of RA accreditation to be better, the socialization of the elaboration of 8 accreditation standards to more than 30 RAs, the training of RA managers in preparing accreditation instruments, RA managers were assisted in compiling RA accreditation instruments, relations were built between RA institutions, the Pekanbaru City Ministry of Religion (RA Supervisor) and BAN PAUD and PNF Riau Province (Assessors), Policy stakeholders welcomed the training and assistance provided.